Desenvolvimento, projeto e análise de fotobiorreatores híbridos em escala piloto - Barrios, Rodrigo Stefanello Bizello (2019)
The technological development for the production of microalgal biomass, configures the search for technologies that are energy efficient and economically viable. The hybrid photobioreactor is the combination of two types of reactors seeking the best configuration of the system, stand out for having greater productivity in microalgal biomass, lower energy consumption, efficient control of physicochemical variations when compared to open type raceway or closed type reactors tubular. The objective of this work was to: (I) perform the scaling up of a hybrid photobioreactor, (II) evaluate the growth kinetics of Scenedesmus obliquus microalgae (CPCC05) in hybrid photobioreactor, (III) operate the hybrid photobioreactor in (IV) to apply the economic technical analysis in hybrid photobioreactor, (V) to establish the life cycle analysis in hybrid photobioreactor, (VI) to extrapolate the discontinuous operation to continuous. In terms of process operating conditions, initial concentration of 100 mg/L and temperatures of 25°C, aeration of 1VVM (Air volume per volume of medium per minute), 15%CO2 and M-8a culture medium were set a ideal for growing of the microalga. The microalga Scenedesmus obliquus presented kinetic performance with maximum cellular concentration of 1775mg/L, in the winter season, at a temperature of 22,3°C a 26,2°C. Concomitantly, the water footprint of the system was 73% return of water used in the production of biomass. The cost required for the construction, operation and maintenance of the system is estimated at 886.08R$/m³. Finally, the results showed that the hybrid photobioreactor has potential of application for the production of microalgae biomass in a sustainable and efficient way.